Fine mapping and sequence analysis reveal a promising candidate gene encoding a novel NB-ARC domain derived from wild rice (Oryza officinalis) that confers bacterial blight resistance - Sinha, Pragya; Kumar T., Dilip; Sk, Hajira; Solanki, Manish; Gokulan, C.G.; Das, Ayyappa; Miriyala, Anila; Gonuguntala, Rekha; Elumalai, Punniakoti; Kousik, M.B.V.N.; S. K., Masthani; Kumboju, Chaitra; et al. (Frontiers Media, 2023)
Bacterial blight disease of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most serious constraints in rice production. The most sustainable strategy to combat the disease is the deployment of host plant resistance. Earlier, we identified an introgression line, IR 75084-15-3-B-B, derived from Oryza officinalis possessing broad-spectrum resistance against Xoo. In order to understand the inheritance of resistance in the O. officinalis accession and identify genomic region(s) associated with resistance, a recombinant inbred line (RIL) mapping population was developed from the cross Samba Mahsuri (susceptible to bacterial blight) × IR 75084-15-3-B-B (resistant to bacterial blight). The F2 population derived from the cross segregated in a phenotypic ratio of 3: 1 (resistant susceptible) implying that resistance in IR 75084-15-3-B-B is controlled by a single dominant gene/quantitative trait locus (QTL). In the F7 generation, a set of 47 homozygous resistant lines and 47 homozygous susceptible lines was used to study the association between phenotypic data obtained through screening with Xoo and genotypic data obtained through analysis of 7K rice single-nucleotide polymorphism (SNP) chip. Through composite interval mapping, a major locus was detected in the midst of two flanking SNP markers, viz., Chr11.27817978 and Chr11.27994133, on chromosome 11L with a logarithm of the odds (LOD) score of 10.21 and 35.93% of phenotypic variation, and the locus has been named Xa48t. In silico search in the genomic region between the two markers flanking Xa48t identified 10 putatively expressed genes located in the region of interest. The quantitative expression and DNA sequence analysis of these genes from contrasting parents identified the Os11g0687900 encoding an NB-ARC domain-containing protein as the most promising gene associated with resistance. Interestingly, a 16-bp insertion was noticed in the untranslated region (UTR) of the gene in the resistant parent, IR 75084-15-3-B-B, which was absent in Samba Mahsuri. The association of Os11g0687900 with resistance phenotype was further established by sequence-based DNA marker analysis in the RIL population. A co-segregating PCR-based INDEL marker, Marker_Xa48, has been developed for use in the marker-assisted breeding of Xa48t.